PENGEMBANGAN MEDIA MAGNET ALFABET (MARGARETA) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS II SDS MUTIARA II - Assifa, Putri Arisyani; Ramadhani, Sulistyani Puteri (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
The aim of education is to improve the early reading skills of second-grade students using the magnetic alphabet media. This study uses the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The subjects of the trial were second-grade students at Mutiara II Private Elementary School. Data collection tools involved performance tests for early reading skills. Data analysis was conducted using the effectiveness test D-Cohen. The results of the study show an improvement in early reading skills before and after using the MARGARETA media, as evidenced by a pretest score of 63.84, which increased to 81.53 on the posttest in the large-scale trial. The effectiveness test D-Cohen resulted in a score of 0.40, which is categorized as moderate. Thus, it can be concluded that the magnetic alphabet media (MARGARETA) is effective in improving the early reading skills of second-grade elementary school students.